2009
DOI: 10.1104/pp.109.148270
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Poplar Wood-Associated NAC Domain Transcription Factors

Abstract: Wood is the most abundant biomass produced by land plants. Dissection of the molecular mechanisms underlying the transcriptional regulation of wood formation is a fundamental issue in plant biology and has important implications in tree biotechnology. Although a number of transcription factors in tree species have been shown to be associated with wood formation and some of them are implicated in lignin biosynthesis, none of them have been demonstrated to be key regulators of the biosynthesis of all three major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
285
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(296 citation statements)
references
References 53 publications
8
285
1
2
Order By: Relevance
“…The expression levels of five NAC genes including PNAC070, 086, 121 and 122 were peaked exclusively in differentiating xylems supported by two independent microarray datasets (Figure 6C and 6G) [87,88]. Among them, PNAC070 (PtWND5A), PNAC086 (PtWND1A) and PNAC008 (PtWND3A) were demonstrated in previous studies as putative redundant homologs involved in Populus wood formation [19]. Interestingly, several genes such as PNAC013, 020 and 120 were preferentially expressed in tissues enriched of secondary cell walls, whereas a subset of genes including PNAC028, 052, 055 and 023 showed constitutively high expressions in both secondary and primary cell wall enriching tissues (Figure 6A-E).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The expression levels of five NAC genes including PNAC070, 086, 121 and 122 were peaked exclusively in differentiating xylems supported by two independent microarray datasets (Figure 6C and 6G) [87,88]. Among them, PNAC070 (PtWND5A), PNAC086 (PtWND1A) and PNAC008 (PtWND3A) were demonstrated in previous studies as putative redundant homologs involved in Populus wood formation [19]. Interestingly, several genes such as PNAC013, 020 and 120 were preferentially expressed in tissues enriched of secondary cell walls, whereas a subset of genes including PNAC028, 052, 055 and 023 showed constitutively high expressions in both secondary and primary cell wall enriching tissues (Figure 6A-E).…”
Section: Resultssupporting
confidence: 61%
“…For example, in accordance with previous findings, a subset of eight genes among the 25 NACs tested were exclusively expressed in differentiating xylem, indicative of their putative roles in secondary cell wall formation. Three genes namely PNAC009 (PtWND4B), PNAC071 (PtWND1B) and PNAC085 (PtWND2B) have been functionally characterized in a recent report [19]. In the present study, PNAC071 gene was shown to primarily express in old root, while microarray profiles indicated the highest transcript abundance in differentiating xylems (Figure 7).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Several transcription factors have been implicated in the control of lignin biosynthesis during formation of secondary xylem (Raes et al, 2003;Zhou et al, 2009;Zhong et al, 2010). NAC domain transcription factors have been implicated in both Arabidopsis (Arabidopsis thaliana) and Populus, including wood-associated NAC domain factors that are functional orthologs of SND1 (for secondary wall-associated NAC domain protein 1; Zhou et al, 2009;Zhong et al, 2010).…”
Section: Transcription Factors and Lignin Biosynthesismentioning
confidence: 99%
“…NAC domain transcription factors have been implicated in both Arabidopsis (Arabidopsis thaliana) and Populus, including wood-associated NAC domain factors that are functional orthologs of SND1 (for secondary wall-associated NAC domain protein 1; Zhou et al, 2009;Zhong et al, 2010). One LIM factor, up to eight MYBs, and a KNOX transcription factor are direct positive and negative regulators of genes in the monolignol biosynthetic pathway, affecting transcript abundance, enzyme activity, and lignin content or composition (S/G ratio; Tamagnone et al, 1998;Kawaoka et al, 2000;Dixon et al, 2002; Mele et al, Figure 3.…”
Section: Transcription Factors and Lignin Biosynthesismentioning
confidence: 99%